2021
DOI: 10.3390/polym13081213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Printing Parameters on Dimensional Error, Surface Roughness and Porosity of FFF Printed Parts with Grid Structure

Abstract: Extrusion printing processes allow for manufacturing complex shapes in a relatively cheap way with low-cost machines. The present study analyzes the effect of printing parameters on dimensional error, roughness, and porosity of printed PLA parts obtained with grid structure. Parts are obtained by means of the fused filament fabrication (FFF) process. Four variables are chosen: Layer height, temperature, speed, and flow rate. A two-level full factorial design with a central point is used to define the experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 39 publications
0
29
1
Order By: Relevance
“…They have concluded that the lower the degree of orientations, the higher the accuracy, and thus the lower the angle for layer deposition. Several studies have focused on improving the dimensional accuracy of 3D-printed parts [32][33][34]. However, in order to increase the application of the FFF process, the strength and mechanical performances of the final parts need to be focused on.…”
Section: Fff Parameters and Their Impact On Part Qualitymentioning
confidence: 99%
“…They have concluded that the lower the degree of orientations, the higher the accuracy, and thus the lower the angle for layer deposition. Several studies have focused on improving the dimensional accuracy of 3D-printed parts [32][33][34]. However, in order to increase the application of the FFF process, the strength and mechanical performances of the final parts need to be focused on.…”
Section: Fff Parameters and Their Impact On Part Qualitymentioning
confidence: 99%
“…Lowest dimensional error was found in experiment three, obtained with low nozzle diameter, high temperature, low layer height, low print speed and low extrusion multiplier. In an earlier paper, higher relative dimensional errors between 0.82% and 2.60% were reported in prismatic porous samples [ 37 ]. In this present work, lower relative dimensional errors were obtained, ranging between 0.036% and 0.625%.…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that print speed (velocity at which the print head moves during printing) does not show a significant impact on the porosity of fused deposition modeling parts (refer to Figure 5 ). This occurs due to the vibrations and errors introduced during the printing process at higher print speed (70 mm/s) led to increased porosity in parts [ 60 ].…”
Section: Resultsmentioning
confidence: 99%